2022
DOI: 10.1155/2022/8163588
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Features of Patients with Drug-Induced Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis in Iran: Different Points of Children from Adults

Abstract: Background. Different epidemiologic aspects of drug-induced Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) in children are scarce. Aim. To compare the clinical and epidemiological features of patients with drug-induced SJS and TEN in children and adults. Method. This retrospective study was conducted at two academic referral centers (Isfahan, Iran) over 5 years. SJS and TEN were clinically diagnosed and confirmed by skin biopsy as needed. Results. One hundred one patients (31 children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…The present analysis observed a trend towards the impact of variable age on SCARs. Many authors also confirmed the role of age on the development of SCARs 31–33 . Even so, most researchers believe that the effect of age was actually just a consequence of the fact that older patients tend to have more drugs and chronic diseases than younger ones.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The present analysis observed a trend towards the impact of variable age on SCARs. Many authors also confirmed the role of age on the development of SCARs 31–33 . Even so, most researchers believe that the effect of age was actually just a consequence of the fact that older patients tend to have more drugs and chronic diseases than younger ones.…”
Section: Discussionmentioning
confidence: 89%
“…Many authors also confirmed the role of age on the development of SCARs. 31 , 32 , 33 Even so, most researchers believe that the effect of age was actually just a consequence of the fact that older patients tend to have more drugs and chronic diseases than younger ones. Therefore, older patients might have a higher possibility of developing SCARs.…”
Section: Discussionmentioning
confidence: 99%
“…SJS is a disease known as a rare occurrence in the world (1–3 cases per 1 000 000 persons) 14 . Additionally, the frequency of pediatric SJS/TEN is very low, but a high rate of long-term complications appears in children with SJS/TEN 15 . Clinical manifestations of SJS/TEN are similar to SARS-CoV-2 infections, including mucosal damage and many dermatological complications including oral lesions 16 , 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Human leukocyte antigen (HLA) risk alleles are known for certain populations and genetic differences in detoxification pathways (cytochrome P450, N-acetylation) can further increase risk. The most commonly associated medications in children are antibiotics and antiepileptics [15 ▪▪ ,57–62]. Acetaminophen (paracetamol) and ibuprofen are often taken for the initial (unrecognized) malaise and prodromal symptoms of DEN and should not be considered the causative medication unless all other possible medications and infections are excluded [15 ▪▪ ,63].…”
Section: Pathogenesis and Etiologymentioning
confidence: 99%
“…The face is often an early area affected by blisters, with rapid progression to involve other body sites in a child with other chronic or acute medical comorbidities necessitating drug therapy. The most common reasons for medication administration in pediatric DEN are infection and seizure disorder [15 ▪▪ ,57–62]; this history can be screened for on intake. Other negative prognostic factors can also be elicited on history including malignancy or stem cell transplantation [67].…”
Section: Clinical Assessmentmentioning
confidence: 99%